EDUKASI PEMANFAATAN OBAT TRADISIONAL SEBAGAI ASI BOOSTER - Andi Ulfah Magefirah Rasyid; Sri Widyastuti; Fityatun Usman; Zulkifli Zulkifli; Syafruddin Syafruddin; Muhammad Taufiq Duppa; Muhammad Guntur; Nurfadilah Nurfadilah; Rahmadani Rahmadani; Sulaiman Sulaiman; Anshari Masri; Ainun Jariah; Andri Anugrah Pratama; Haryanto Haryanto (Bajang Institute, 2022)
Various types of plants in the surrounding environment that have medicinal properties are many that can be obtained and utilized, and can even be planted themselves, which are known as family medicinal plants. This medicinal plant has begun to be widely studied, especially Indonesian Native Medicinal Plants, because it has relatively small side effects when compared to modern medical drugs. Communities in Pattallassang District generally have various types of medicinal plants that are planted in their yards and are often used as alternative treatments for certain types of diseases or as supplements, one example being breastfeeding boosters, which are very much needed by mothers in carrying out their activities. exclusive breastfeeding program. To support the exclusive breastfeeding program, various efforts must be made, one of which is the use of breastfeeding boosters, which is expected to help increase the production of breast milk. The purpose of the community service activity is to increase understanding of the importance of exclusive breastfeeding and to provide education about the use of several plants that have the potential as breastfeeding boosters in terms of processing techniques and more rational ways of using them. This service is carried out at Merpati Posyandu, Pattallassang Village, Pattallassang District, Takalar Regency. The method of providing community service activities is by providing counseling and demonstrations on how to process and manufacture good traditional medicines. The results of the activity assessment showed that participants gained knowledge about the types of traditional medicines, especially breastfeeding boosters, along with good processing and manufacturing methods of traditional medicines.